2015
DOI: 10.1039/c5ta07898a
|View full text |Cite
|
Sign up to set email alerts
|

Soft X-ray spectroscopic studies of the electronic structure of M:BiVO4(M = Mo, W) single crystals

Abstract: X-ray spectroscopy reveals the presence of inter-band gap electronic states of egsymmetry in M:BiVO4(M = Mo, W) PEC anodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
59
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(75 citation statements)
references
References 40 publications
(116 reference statements)
15
59
1
Order By: Relevance
“…2 (b) and indicate the presence of V 5+ in monoclinic scheelite structure of BiVO4. 11,30 It is immediately clear that the L3 edge, shows increased spectral weight at higher energies (just above the t2 peak) for E||ab relative to E||c. This observation is also evident at the L2 edge.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 (b) and indicate the presence of V 5+ in monoclinic scheelite structure of BiVO4. 11,30 It is immediately clear that the L3 edge, shows increased spectral weight at higher energies (just above the t2 peak) for E||ab relative to E||c. This observation is also evident at the L2 edge.…”
Section: Resultsmentioning
confidence: 99%
“…11 Note that survey and O 1s spectra collected after 300 o C heat treatment in a 1×10 -6 Torr oxygen atmosphere are shown in Supplementary Fig. 1 (a)-(b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17][18][19] The underlying origin of the observed performance improvement remains an active area of investigation, with spectroscopic studies indicating a decrease in electron trap state concentration producing an increase in electron and hole mobilities 10 and/or increased charge carrier concentration induced by electron donating elements, in particular W and Mo. 20 Changes in the band gap and movement of band edges have also been reported. 21 Several combinatorial studies have contributed to this broad mBiVO4 alloying effort through systematic variation of alloy concentration using wet chemical synthesis or physical vapor deposition techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Through the RIXS investigations, the aforementioned blue-shift of the X-ray emission, which corresponds to the occurrence of the indirect bandgap, has been seen in diamond, Be chalcogenides, metal doped and pristine BiVO 4 , and Fe 2 O 3 . [37][38][39][40][41] To further demonstrate the correlation between size and band gap we refer to previous studies on the electronic properties of Fe 2 O 3 by Vayssieres et al 40,42 Previously, observed at the high emission energy region. The blue-shift of the emission spectra is a strong indication that Fe 2 O 3 is an indirect bandgap semiconductor.…”
Section: Studies Of Pristine 3d Tmos: Size Effects On the Tio 2 Fe mentioning
confidence: 99%